Influenza B associated paediatric acute respiratory infection hospitalization in central vietnam - Yoshihara, Keisuke (Influenza Other Respir Viruses, 2019)
BACKGROUND: Influenza B is one of the major etiologies for acute respiratory infections (ARI) among children worldwide; however, its clinical‐epidemiological information is limited. We aimed to investigate the hospitalization incidence and clinical‐epidemiological characteristics of influenza B‐associated paediatric ARIs in central Vietnam. METHODS: We collected clinical‐epidemiological information and nasopharyngeal swabs from ARI children hospitalized at Khanh Hoa General Hospital, Nha Trang, Vietnam from February 2007 through June 2013. Nasopharyngeal samples were screened for 13 respiratory viruses using Multiplex‐PCRs. Influenza B‐confirmed cases were genotyped by Haemagglutinin gene sequencing. We analyzed the clinical‐epidemiological characteristics of influenza B Lineages (Victoria/Yamagata) and WHO Groups. RESULTS: In the pre‐A/H1N1pdm09 period, influenza B‐associated ARI hospitalization incidence among children under five was low, ranging between 14.7 and 80.7 per 100 000 population. The incidence increased to between 51.4 and 330 in the post‐A/H1N1pdm09. Influenza B ARI cases were slightly older with milder symptoms. Both Victoria and Yamagata lineages were detected before the A/H1N1pdm09 outbreak; however, Victoria lineage became predominant in 2010‐2013 (84% Victoria vs 16% Yamagata). Victoria and Yamagata lineages did not differ in demographic and clinical characteristics. In Victoria lineage, Group1 ARI cases were clinically more severe compared to Group5, presenting a greater proportion of wheeze, tachypnea, and lower respiratory tract infection. CONCLUSIONS: The current results highlight the increased incidence of influenza B‐related ARI hospitalization among children in central Vietnam in the post‐A/H1N1pdm09 era. Furthermore, the difference in clinical severity between Victoria lineage Group1 and 5 implies the importance of influenza B genetic variation on clinical presentation.